Machine learning fundamentals with Amazon SageMaker on AWS : LiveLessons (LiveLessons (Indianapolis, Ind.), 2020)
"Machine Learning Fundamentals with Amazon SageMaker on AWS LiveLessons teaches the fundamental concepts and taxonomy for machine learning. It provides specific scenarios, so the user can determine if ML would be beneficial. The course also provides a high-level overview of the tools, languages, and libraries that Amazon SageMaker uses, including the AWS console, Jupyter Notebooks, languages such as Python, and interactive data analysis libraries such as Pandas. This course will also discusses common algorithms and models used with ML and Amazon SageMaker, which will help determine the appropriate model to use in specific business scenarios. Through this course the user will walk through Amazon SageMaker's end-to-end workflow using practical and pragmatic business scenarios. You'll see how you can benefit from the ability of a machine to make predictions on future data through hands-on labs and key concepts. AWS is continuing to make great strides to innovate their Artificial Intelligence and Machine Learning Platform. The concepts learned in this course will provide you with the foundation to build your own innovative systems on this dynamic platform."--Resource description page